Where is the Boundary Between Sociology and Not-Sociology? - Platt, Jennifer (Serendipities. Journal for the Sociology and History of the Social Sciences, 2016)
In work on the history of sociology, how may the boundaries of study be defined, and what requires explanation as part of sociology? Becker’s concept of the „art world’ suggests thinking in terms of the „sociology world’ which is needed to produce the sociological object. Three very different examples – Young and Willmott’s Family and Kinship in East London, a cross-disciplinary quantitative sociology study group, and Hodson’s use of amateur descriptions of workplaces as data – are discussed, and it is concluded that the practical methodological answer depends on the particular research topic and the resources available.